PP.28.03: GENETIC MULTIFACTORIAL AND MULTILOCUS STUDY IN A PORTUGUESE POPULATION WITH CORONARY DISEASE. (June 2015) - Pereira, A.; Reis, R. Palma dos; Gomes, S.; Rodrigues, R.; Ferreira, R.; Sousa, A.C.; Freitas, S.; Henriques, E.; Borges, S.; Freitas, A.I.; Guerra, G.; Ornelas, I.; et al.
Abstract : Objective: Approximately 15% of patients who develop coronary artery disease (CAD) have reduced stratified cardiovascular risk by existing predictive models. It is estimated that, for CAD, the genetic variation explains 40–55% of this variability. Characterize the genetic profile of a representative sample of the Portuguese population, including genetic polymorphisms associated with traditional cardiovascular risk factors (TCRF) and Coronary Atherosclerosis. Design and method: A case-control study included 1321 patients with documented CAD (mean age 53.4 ± 8.1 years, 78.8% male) and 1148 controls, selected from our database in order to be similar to cases in terms of gender and age. We evaluated the TCRF and 29 genes variants: ACE I/D, AGT235 M/T, ATIR A/C, MTHFR C/T and 1298 A/C, PON192 Q/R and 55 L/M, LPA T/C, APO E, Locus 9p21.3 (rs1333049), CDKN2B (rs4977574), GJA4 C/T, PCSK9 A/G, TAS2R50 A/G, KIF6 C/T, IGF2BP2 G/T, ADAMTS7 A/G, MC4R T/C, PPARG Pro12 Ala, ZNF259 C/G, SMAD3 C/T, MIA3 C/A, MTHFD1L A/G, SLC30A8 C/T, TCF7L2 C/T, HNF4 C/G, FTO A/C and ADIPOQ C/G. A score was created based on the risk multiplication (Odds Ratio) of each genotype of the 29 variants. A logistic regression was performed to estimate the CAD risk according to the score deciles. The decile, which included the median of the genetic score of the study population, was considered as the reference class. Results: The genetic Score ranged between 0.04 and 6.7 and the median of the population was 0.369. Low values of genetic Score were significantly protective (first 2 deciles, OR = 0.464 p < 0.570 and OR < 0.0001 p = 0.002, respectively). On the other hand, high score values showed a significant CAD risk (last 2 deciles, OR = 1.455 p = 0.042 and OR = 1.620 p = 0.009, respectively), while intermediate values were not significant. Figure. No caption available. Conclusions: This global genetic score, mainly in its extreme values, allows the prediction of the probability of the development, or not, of CAD and also allows that the genetic risk have similar weight to one of the traditional risk factors.